Prevention of amino acid losses during peritoneal dialysis. - Jackson, M. A. (BMJ Group, 1979)
The addition of amino acid supplements to peritoneal dialysis fluid has been studied in 8 patients with compromised renal function requiring peritoneal dialysis. By the addition of 10 ml of Vamin-glucose solution to each one litre of peritoneal dialysate, amino acid losses were curtailed, no significant alterations occurred in the plasma amino acid concentrations, there were no local complications and no infections were seen. This procedure is recommended as a safe, simple way of keeping a patient in positive amino acid balance during peritoneal dialysis.